2000
DOI: 10.2175/106143000x137103
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Inhibition Kinetics of Phenol Biodegradation

Abstract: Phenol biodegradation was studied in batch experiments using an acclimated inoculum and initial phenol concentrations ranging from 0.1 to 1.3 g/L. Phenol depletion and associated microbial growth were monitored over time to provide information that was used to estimate the kinetics of phenol biodegradation. Phenol inhibited biodegradation at high concentrations, and a generalized substrate inhibition model based on statistical thermodynamics was used to describe the dynamics of microbial growth in phenol. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
1
23
1
2
Order By: Relevance
“…However, due to their toxicity, microbial degradation of phenolic compounds is usually inhibited at high concentrations (Goudar et al, 2000;Choi and Gu, 2001;Goudar and Delvin, 2001;Acuña-Argüelles et al, 2003;Oboirien et al, 2005;Okpokwasili and Nweke, 2006). In order to evaluate pollution risk of phenolic compounds in wastewater, it is important to assess their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their toxicity, microbial degradation of phenolic compounds is usually inhibited at high concentrations (Goudar et al, 2000;Choi and Gu, 2001;Goudar and Delvin, 2001;Acuña-Argüelles et al, 2003;Oboirien et al, 2005;Okpokwasili and Nweke, 2006). In order to evaluate pollution risk of phenolic compounds in wastewater, it is important to assess their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Phenol is difficult to use as a substrate for growth within biodegradable process because the phenol inhibits the activity of innate of most kinds of microorganisms at lower and higher concentrations, also the phenol is toxic to microbial even at skimpy concentration [22]. Moreover, Goudar et al [10] reported that the greater than 1.3 g/L of phenol concentrations were toxic to the culture of microbial. Conversely, phenol showed inhibition to degradation rate of substrate and specific rate of growth over initial concentration of phenol 300 mg/L [23].…”
Section: Determination Of Biomass Concentrationmentioning
confidence: 99%
“…Although the phenol is a poisonous composite which inhibits its possess change even at low concentrations, there are some methods accessible for phenol treatment; the biological treatment is mainly attractive because it has the significant to complete degrade phenol at often with generating minimum production of secondary waste and safe end products [10]. The simple recycle of the biomass by both, chemical and physical methods have been recognized for aromatic wastewaters treatment, but phenols biological degradation is progressively more being documented as a proficient and mild effective cost method [11].…”
Section: Introductionmentioning
confidence: 99%
“…Andrews (1968) was the first to propose an equation to model substrate-inhibited microbial growth and his model provided a good fit to the experimental data and has been widely used particularly for wastewater treatment systems (Sokol, 1987;Grady & Lim, 1999;Tang & Fan, 1987;Rozich & Gaudy Jr, 1985;Goudar et al, 2000;Tan et al, 1996). Andrew's equation was basically an extension of the Monod model (Monod, 1949) where an additional substrate inhibition term has been included (S 2 /K I ).…”
Section: Introductionmentioning
confidence: 99%